Determinants of intention to use Islamic mobile banking: Evidence from millennial generation - Muamar Nur Kholid (Jurnal Ekonomi & Keuangan Islam, 2019)
This research aims to identify factors affecting the intention of millennial customers to use the Islamic Mobile Banking (IMB). This research applies the Unified Theory of Acceptance and Use of Technology (UTAUT) with two additional variables namely perceived risk and perceived financial cost. The data of the research are from 142 respondents of the millennial generation. The research uses SmartPLS 2.0. The results reveal that the perceived risk and perceived financial cost significantly and negatively affect the intention to use the IMB. Meanwhile, the performance expectancy and effort expectancy significantly and positively affect the intention to use the IMB. The other two variables namely social influence and facilitating condition do not show any significant effect on the intention to use the IMB. Furthermore, this research discusses the impact of the results of the research, both in the theoretical and practical contexts.